2021
DOI: 10.3390/cancers13040638
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Expression Is Predictive of Survival in Cetuximab Treated Patients with RAS Wild Type Metastatic Colorectal Cancer

Abstract: The overexpressed HER2 is an important target for treatment with monoclonal antibody (mAb) trastuzumab, only in patients with breast and gastric cancers, and is an emerging therapeutic biomarker in metastatic colorectal cancer (mCRC) treated with anti-epidermal growth factor receptor (EGFR) mAbs cetuximab and panitumumab. In this study, we investigated the relative expression and predictive value of all human epidermal growth factor receptor (HER) family members in 144 cetuximab-treated patients with wild type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Moreover, KRAS is the most common form of mutated oncogene in cancer, and the frequency of KRAS mutations is particularly high in colorectal, pancreatic, and lung cancers [ 24 26 ]. Cetuximab, an EGFR-targeting agent, is a standard treatment for KRAS wild-type mCRC [ 27 ]. KRAS mutant CRC cells have been reported that it could promote tumour progression and induce resistance to cetuximab therapy [ 28 ]; however, there is no effective treatment to specifically treat cancers expressing KRAS mutations [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, KRAS is the most common form of mutated oncogene in cancer, and the frequency of KRAS mutations is particularly high in colorectal, pancreatic, and lung cancers [ 24 26 ]. Cetuximab, an EGFR-targeting agent, is a standard treatment for KRAS wild-type mCRC [ 27 ]. KRAS mutant CRC cells have been reported that it could promote tumour progression and induce resistance to cetuximab therapy [ 28 ]; however, there is no effective treatment to specifically treat cancers expressing KRAS mutations [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“… d Assumed from KM curve follow-up. e The HR for OS in Khelwatty et al 29 was inconsistent, the lower CI was higher than HR value (HR, 0.21 [95% CI, 0.62-0.73]), and it was excluded from the OS analysis. Study authors were contacted to clarify the data but no response was received.…”
Section: Resultsmentioning
confidence: 99%
“…Some heterogeneity in the HER2 detection method and HER2-positivity criteria utilized in each study was identified. All patients received anti-EGFR treatment, either as monotherapy or in combination with standard chemotherapy, and with the exception of Khelwatty et al, 29 across different lines of therapy ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This result might be the consequence of biological characteristics not measured in the clinical practice in RAS/BRAF wild-type patients, such as APC mutations, which confer worse prognoses more frequently found in EOCRC [27]. Other alterations are known to be bad prognostic factors in the RAS/BRAF wild type, but to our knowledge, they have not been described as being more prevalent in EOCRC patients, such as PIK3CA mutations (a known negative predictor of response to EGFR inhibitors in RAS wild-type tumors [28]) and HER2 status (its expression in the membrane of the tumor cells is associated with a shorter progression-free survival (PFS) to EGFR inhibitors) [29]. Whether ultraselection of RAS/BRAF wild-type patients is the key to improving prognosis in this population is yet to be determined [30,31].…”
Section: Discussionmentioning
confidence: 99%